Using Elecsys® HIV Combi PT assay to identify acute and early HIV infection in a teaching hospital of southwest China. (March 2016) - Zhu, Siyuan; Li, Dongdong; An, Jingna; Chen, Qixia; Liu, Qianqian; Tao, Chuanmin
This study is the first attempt to evaluate the use of the Elecsys® HIV combi PT assay in identifying acute and early HIV infection in southwest China. We also analyzed the extent of cutoff ratios overlap between false-positive and true-positive results to aid the identification of HIV infection, using samples from the West China Hospital in Chengdu, Sichuan Province from April 2012 to December 2013. Reactive results from a screening test were retested and all repeatedly reactive samples – if available – were confirmed with Western blot, HIV-1 p24 antigen, or HIV-1 RNA. Of 241, 840 samples screened, the Elecsys® HIV combi PT assay identified 54 patients with acute and early HIV infection; 99.8% cases with cutoff index ratios ≥50 were proved to be true-positive HIV infection and 95.6% cases with cutoff index ratios <15 were falsely positive. In conclusion, the Elecsys® HIV combi PT assay can identify acute and early HIV infection, including those who might have been missed by third-generation HIV screening assays and Western blot. However, cutoff index ratios <15 are not always false-reactive results; a definitive result cannot be attained without further confirmation. In resource-poor regions where a HIV-1 nucleic acid test may be unaffordable, detection of HIV-1 p24 antigen can be an alternative strategy to diagnose HIV infection in individuals with a negative or indeterminate Western blot.